Investigation on the Effect of Dynamic Frequency on Fracture Evolution in Preflawed Rock under Multistage Cyclic Loads: Insight from Acoustic Emission Monitoring - H. J. Meng; Y. Wang; B. Zhang; S. H. Gao (Geofluids)
This study is aimed at revealing the effect of dynamic loading frequency on the fracture evolution behavior in preflawed rock samples under multistage cyclic loading conditions. The fracture evolution characteristics were investigated using stress-strain descriptions and in situ acoustic emission techniques. It is shown that rock strength, deformation, AE pattern, and fatigue life are strongly affected by the applied dynamic loading frequency. Rock fatigue strength and lifetime increase with the increase of dynamic loading frequency. The AE count and energy output both increase with the increase of the applied loading frequency. Six kinds of cracking modes were revealed by AE spectral frequency analysis. It is shown that large-scaled cracks are easy to be formed for rock subjected to high-frequency loads, reflected as the deceasing of AE signals with high-frequency–high-amplitude signal feature. It is suggested that applied dynamic loading frequency has obvious impact on the crack coalescence at the rock bridge segment. The testing results are helpful to enhance the cognitive of the influence of dynamic frequency on the crack communication behavior and can be expected to predict the stability of rock mass structures where rock mass is subjected to fatigue loading.